2018
DOI: 10.4014/jmb.1709.09070
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Gut Microbiota of Freshwater Shrimp and Its Associations with the Surrounding Microbiota and Environmental Factors

Abstract: The gut microbiota of aquatic animals plays a crucial role in host health through nutrient acquisition and outcompetition of pathogens. In this study, on the basis of the highthroughput sequencing of 16S rRNA gene amplicons, we examined the bacterial communities in the gut of freshwater shrimp (Macrobrachium nipponense) and in their living environments (sediment and pond water) and analyzed the effects of abiotic and biotic factors on the shrimp gut bacterial communities. High bacterial heterogeneity was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…Our SEM results showed that water salinity, temperature and DO are determinants in driving the successions in shrimp gut microbiota (Fig. 5), corroborating previous findings obtained in shrimp gut systems (Zhao et al, 2018;Xiong et al, 2018a). The noteworthy finding is that, when compared with bacterioplankton community, water variables shaped the shrimp gut microbiota by conjointly direct and indirect effects (Supporting Information Table S3).…”
Section: Factors Govern the Shrimp Gut Microbiotasupporting
confidence: 89%
See 2 more Smart Citations
“…Our SEM results showed that water salinity, temperature and DO are determinants in driving the successions in shrimp gut microbiota (Fig. 5), corroborating previous findings obtained in shrimp gut systems (Zhao et al, 2018;Xiong et al, 2018a). The noteworthy finding is that, when compared with bacterioplankton community, water variables shaped the shrimp gut microbiota by conjointly direct and indirect effects (Supporting Information Table S3).…”
Section: Factors Govern the Shrimp Gut Microbiotasupporting
confidence: 89%
“…The large proportion of 'unknown' source could be colonized into the gut from other environmental sources that we did not investigate, such as vertical transmission, sedimentary biofilm, food or shrimp care staff. However, ample evidence has shown that the bacterial communities in shrimp gut are significantly distinct from these in rearing water and sediment (Xiong et al, 2015;Cornejo-Granados et al, 2017;Hou et al, 2018;Zhao et al, 2018). Alternatively, these 'unknown' bacteria were present in the rearing water but undetected here.…”
Section: Little Shrimp Gut Microbiota Sourcing From Rearing Watermentioning
confidence: 82%
See 1 more Smart Citation
“…The results of artificial conditions in the laboratory are essential to understanding the growth characteristics in outdoor cultures [27]. The culture was non-axenic, which is associated with bacteria present in the natural environment and cultured with algae [16]. Besides, the non-axenic microalgae cultures are applied in the green-water technique, and it is important to recognize the microbiota associated with the microalgae cultures [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, since the bacterial communities are difficult to observe directly, they are first separated by isolation and then analyzed using methods such as clone libraries or RFLP [14,15], which requires a lot of time and effort. Next-generation sequencing (NGS) is a technique used to quickly analyze microbiota in detail without isolating the microorganism separately [16,17]. There are two ways; the first is a nucleotide sequence analysis targeting 16S rRNA and the second is a shotgun method.…”
Section: Introductionmentioning
confidence: 99%